2015
DOI: 10.1136/jclinpath-2014-202807
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin

Abstract: Procalcitonin (PCT) is the 116 amino acid precursor of the hormone calcitonin, produced by the C cells of the thyroid. Its synthesis is upregulated in bacterial infection and downregulated by viral infection. Consequently, with the increasing development of antibiotic resistance, interest has focused on the ability of this marker to not only diagnose infection but to tailor antibiotic treatment and help reduce the development of antibiotic resistance. The value of PCT depends on the specific clinical situation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 49 publications
1
70
1
5
Order By: Relevance
“…PCT is an inflammatory factor without hormone activity; it is the most useful biomarker, and it is better than other indicators for hyper endotoxemia [15]. The release of various inflammatory cytokines in SAP patients will lead to secondary injuries in various tissues and organs.…”
Section: Discussionmentioning
confidence: 99%
“…PCT is an inflammatory factor without hormone activity; it is the most useful biomarker, and it is better than other indicators for hyper endotoxemia [15]. The release of various inflammatory cytokines in SAP patients will lead to secondary injuries in various tissues and organs.…”
Section: Discussionmentioning
confidence: 99%
“…Procalcitonin is produced by liver and kidney cells, adipocytes and myocytes, in response to inflammation or infection [24,25]. Even though it is considered as a marker of bacteria-associated sepsis, an increase in its concentration has been reported in SIRS without infection, such as in the case of severe trauma and burns [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…PCT is an inflammatory factor without hormonal activity with relative molecular weight of 13,000 kDa and half-life of ~24 h. Several studies have suggested that PCT is the most useful biomarker for diagnosis of septicopyemia, with precedence over other laboratory indicators (12). PCT levels are very low in healthy subjects, and are almost undetectable (<0.0025 Ug/ml) (13).…”
Section: Discussionmentioning
confidence: 99%